Improving the Quality of Education Through Revitalization of Educational-Based Libraries as an Effort to Increase Literacy and Sustainability of Reading Corners - Dian Sonya Kristanti; Syarif Hidayatullah Azhumatkhan; Ardhan Ardiansyah Kawakibi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Reading interest plays a crucial role in students' cognitive development and academic achievement. However, the low access to interesting reading materials and the lack of library facilities are the main obstacles in improving the literacy of elementary school students. This study aims to identify the impact of educational-based library revitalization on increasing students' interest in reading at SDN Sukolilo 01. The method used is Classroom Action Research (PTK) with a spiral approach from Kemmis and Taggart, which includes planning, action, observation and reflection. The implementation of the creative library program included library rearrangement, interactive reading, and literacy activities. The results showed a significant increase in library visits, book borrowing and student participation in literacy activities. The main obstacles faced were the limited book collection and students' low interest in non-fiction books. Therefore, there is a need for collection enrichment and innovative strategies to sustain the reading culture in the long term. This study contributes to providing recommendations for schools in creating a more interactive and sustainable literacy environment.